Кон Katherine Liepe-Levinson, Strip Show: Performances of Gender and Desire: Për Katherine Liepe-Levinson, Strip Show: Performances of Gender and Desire - Badarevski, Bobi; Ahmeti, Lindita (Identities: Journal for Politics, Gender and Culture, 2004)
Author(s): Bobi Badarevski | Боби Бадаревски Title (Macedonian): Кон Katherine Liepe-Levinson, Strip Show: Performances of Gender and Desire Title (Albanian): Për Katherine Liepe-Levinson, Strip Show: Performances of Gender and Desire Translated by (Macedonian to Albanian): Lindita Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 1 (Summer 2004) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 237-238 Page Count: 2 Citation (Macedonian): Боби Бадаревски, „Кон Katherine Liepe-Levinson, Strip Show: Performances of Gender and Desire“, Идентитети: списание за политика, род и култура, т. 3, бр. 1 (лето 2004): 237-238. Citation (Albanian): Bobi Badarevski, „Për Katherine Liepe-Levinson, Strip Show: Performances of Gender and Desire“, përkthim nga Maqedonishtja Lindita Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 1 (Summer 2004): 237-238.